PENGARUH CONTENT MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN SEPATU SANDAL CARVIL PADA APLIKASI TIKTOK - Sultony, Yanuar Bhakti; Soebiantoro, Ugy (JURNAL LENTERA BISNIS, 2026)
Social media has become a dominant and effective marketing tool. TikTok, originally known as an entertainment medium, has now transformed into a powerful e-commerce channel. PT Carvil Abadi, an Indonesian shoe and sandal brand, had established itself as a market leader, but experienced a significant decline in market share in 2024 and was challenged by other brands. The main objective of this study is to analyze the influence of content marketing and online customer reviews on purchasing decisions for Carvil sandals on the TikTok app. Data collection was conducted quantitatively using a survey method. A total of 100 respondent as TikTok users and having purchased Carvil sandals participated in the study's questionnaire. The data were processed and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings of this study indicate that content marketing and online customer reviews influence purchasing decisions. This suggests that companies need to improve and promote the quality of digital content and pay attention to the influence of consumer reviews to improve purchasing decisions.